2019
DOI: 10.1007/s00381-019-04138-8
|View full text |Cite
|
Sign up to set email alerts
|

Severe bacterial meningitis due to an enterothecal fistula in a 6-year-old child with Currarino syndrome: evaluation of surgical strategy with review of the literature

Abstract: Meningitis is a rare but serious complication in patients with Currarino syndrome. We present a 6-year-old girl with a fulminant meningitis due to an enterothecal fistula involving the anterior sacral meningocele. Initial treatment consisted of broad-spectrum intravenous antibiotic therapy and laparoscopic construction of a deviating double-loop ileostomy. This was followed by an elective posterior neurosurgical approach with a sacral laminectomy, evacuation of the empyema, and securing the disconnection of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Most of the cases and studies performed previously in our hospital identified only mono-bacterial anaerobe meningitis [ 36 , 37 ]. Moreover, only a few case reports of polymicrobial mixed aerobe–anaerobe meningitis have been published worldwide [ 1 , 33 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the cases and studies performed previously in our hospital identified only mono-bacterial anaerobe meningitis [ 36 , 37 ]. Moreover, only a few case reports of polymicrobial mixed aerobe–anaerobe meningitis have been published worldwide [ 1 , 33 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified a total of 15 reported cases of polymicrobial mixed aerobe–anaerobe meningitis. Most of the cases were enterogenic meningitis, mainly in patients with Currarino syndrome or anterior sacral meningocele [ 1 , 32 , 35 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Only four cases of polymicrobial mixed aerobe–anaerobe meningitis secondary to ENT (sinusitis, mastoiditis) infections were reported.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have only been cases of enterothecal fistula described in the pediatric population or cases described in patients with Currarino syndrome, which is an autosomal dominant hereditary condition characterized by a triad of sacral agenesis abnormalities, anorectal malformation, and a presacral mass. In a 2019 case report, Jeltema et al described this phenomenon in a 6-year-old patient with history of Currarino syndrome resulting in partial sacral agenesis, anorectal malformation, and anterior meningocele ( 4 ). This patient was treated with a diverting loop ileostomy, and the dural defect was found to have spontaneously closed without additional intervention.…”
Section: Discussionmentioning
confidence: 99%